PENDIDIKAN VOCATIONAL SKILLS: Di Pondok Pesantren Darussalam Kersamanah Garut - Hadiwijaya, Denden Sudarman; Hadiwijaya, Ahmad Hilal (Prodi PAI IAILM Suryalaya, 2019)
This article aims to determine how important the vocational skill education for students in the Darussalam Islamic Boarding School of Kersamanah Garut. The background of this research is that ideally the person who was educated both formal and non-formal schools at least have the skills of life that it faces, especially in the world of work. In fact there are a lot of unemployment among educated either issued by the formal and non-formal education is still unused and still many educational institutions interventioned with offices and civil service, and there are still doubts in the world of work on the output issued boarding. Therefore it is necessary to study